Analisis Faktor Latar Belakang Pendidikan Menengah Dalam Penguasaan Matematika Dasar Mahasiswa Baru Teknik Sipil Dan Teknik Pertambangan Di Kota Gunungsitoli - Zendarato, Idelman Zundrianto; David Ardian Gea; Hamedoni Harita (CV. SINAR HOWUHOWU, 2026)
Basic mathematics is one of the main foundations in higher education, especially for students majoring in engineering fields such as civil engineering and mining engineering. Mastery of basic mathematical concepts is an important prerequisite for understanding advanced material in engineering, such as mechanics, structural analysis, numerical modelling, and other engineering calculations. Inaccurate understanding at this early stage has the potential to cause difficulties in solving quantitative and complex engineering problems in the future (Aida, 2021). This study uses a descriptive analytical method with a quantitative approach to describe and analyse the use of basic mathematics in calculating road material requirements and to evaluate its effectiveness. The research population consists of road construction projects in Indonesia in the last five years, with samples taken using purposive sampling from representative projects. The results show that the secondary education backgrounds of new students in the Civil Engineering and Mining Engineering Study Program in Gunungsitoli City are heterogeneous. Students came from various types of schools, namely senior high schools majoring in natural sciences, senior high schools not majoring in natural sciences, and vocational high schools with various expertise programmes. These differences in educational backgrounds had an impact on the variation in students' mastery of basic mathematics at the beginning of their studies. Based on the research results and discussion, it can be concluded that secondary education background plays an important role in determining the level of basic mathematics mastery of new students in the Civil Engineering and Mining Engineering Study Program in Gunungsitoli City. Differences in the types of schools attended, the curricula followed, and the intensity of mathematics learning at the secondary education level cause students to enter university with varying levels of initial mathematics ability.